Speech perception in children with cochlear implants - Mildner, Vesna (Array, 2006)
A total of 52 different one- and two-syllable Croatian words were presented auditorily in a forced choice minimal-pair discrimination task, accompanied by visual presentation on computer screen. There were 68 stimuli that wereminimal pairs either with respect to the vowel or in the case of consonants, with respect to place of articulation, manner of articulation or voicing. 29 children were asked to repeat the word and point to the picture of the apropriate object. Vowels were the most correctly discriminated. There were more confusions between closer vowels than between more distant ones. The children had the highest percentage of correct responses to affricates, followed by fricatives and stops. It seems that a combination of early implantation and rehabilitation, together with long and continuous therapy and substantially improved post-operative hearing level make a good foundation but are by no menas the only prerequisites for a satisfactory outcome of therapy.